2015
DOI: 10.3109/08958378.2015.1045051
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5-rich dust collected from the air in Fukuoka, Kyushu, Japan, can exacerbate murine lung eosinophilia

Abstract: PM2.5 can exacerbate asthma. Organic substances adsorbed on PM2.5-rich dust (PM2.5rd) were inactivated by heating at 360 °C. To characterize the role of organic substances, the effects of PM2.5rd and heated PM2.5-rich dust (H-PM2.5 rd) on allergic lung inflammation were investigated. BALB/c mice were intratracheally administered PM2.5rd or H-PM2.5rd with or without ovalbumin (OVA) four times at 2-week intervals. PM2.5rd, but not H-PM2.5rd, caused neutrophilic alveolitis and bronchitis. In the presence of OVA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…TLRs in host cells could sense the stimulus and induce the synthesis of pro-IL-1β41. Some in vitro studies also revealed that TLR4 mainly contributed to cytokines production induced by PM 2.5 42. Activated NLRP3 inflammasome activates caspase-1 which subsequently cleaves pro-IL-1β into the mature form, IL-1β4344.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs in host cells could sense the stimulus and induce the synthesis of pro-IL-1β41. Some in vitro studies also revealed that TLR4 mainly contributed to cytokines production induced by PM 2.5 42. Activated NLRP3 inflammasome activates caspase-1 which subsequently cleaves pro-IL-1β into the mature form, IL-1β4344.…”
Section: Discussionmentioning
confidence: 99%
“…PAHs were analyzed according to a previously reported method (He et al ., , , ,b). Briefly, samples collected in the Teflon filter were extracted twice with a 20 ml portion of dichloromethane at 15°C by ultrasonic extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Six mice from each group were used to examine the free cell contents from BALF. BALF and cell counts were determined in the same manner as detailed in previous studies (He et al ., , , , ,b,c). In brief, tracheas were cannulated after the collection of blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, PM2.5 was collected. PM2.5 “Kitakyushu Apr 2011” (PM2.5‐rich dust, with 83% PM2.5) was collected using a high‐volume air sampler (Sibata Scientific Technology, Taito‐ku, Japan) with a Teflon filter (He et al, ). The remaining four samples of PM2.5 from Shenyang were collected using a four‐stage multi‐nozzle cascade impactor (Tokyo Dyle, Tokyo, Japan) (He et al, ).…”
Section: Methodsmentioning
confidence: 99%